Fast Mode Decision Algorithm for Depth Coding in 3D Video Systems Using H.264/AVC - Yoon, Da-Hyun; Ho, Yo-Sung (Advances in Image and Video Technology, 2011)
Complexity of multiview coding is proportional to the number of cameras. It makes difficult to implement multiview sequences in real applications. Thus, we propose a fast mode decision algorithm for both intra and inter prediction to reduce the computational complexity of H.264/AVC for depth video coding. By analyzing the depth variation, we classify the depth video into depth-continuity and depth-discontinuity regions. We determine a threshold value for classifying these regions by experiments. Since the depth-continuity region has an imbalance in the mode distribution, we limit the mode candidates. Experimental results show that our proposed algorithm reduces the encoding time by up to 78% and 84% for the intra and inter frames, respectively, with negligible PSNR loss and slight bit-rate increase, compared to JMVC 8.3.